2000
DOI: 10.1074/jbc.m001676200
|View full text |Cite
|
Sign up to set email alerts
|

NIPP1-mediated Interaction of Protein Phosphatase-1 with CDC5L, a Regulator of Pre-mRNA Splicing and Mitotic Entry

Abstract: NIPP1 is a regulatory subunit of a species of protein phosphatase-1 (PP1) that co-localizes with splicing factors in nuclear speckles. We report that the N-terminal third of NIPP1 largely consists of a Forkhead-associated (FHA) protein interaction domain, a known phosphopeptide interaction module. A yeast two-hybrid screening revealed an interaction between this domain and a human homolog (CDC5L) of the fission yeast protein cdc5, which is required for G 2 /M progression and pre-mRNA splicing. CDC5L and NIPP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
119
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 40 publications
5
119
0
1
Order By: Relevance
“…Phosphatases, including PP1 [173][174][175][176][177][178][179][180], PP2C-gamma [181,182], PP2A [178,183], and the pol II CTD phosphatase FCP1 [184], also interact with splicing factors or are known to control splicing. Of these, PP2A binds CaMK IV in a signalling complex [185,186].…”
Section: Splicing Factors Regulated By Ca ++ Signalsmentioning
confidence: 99%
“…Phosphatases, including PP1 [173][174][175][176][177][178][179][180], PP2C-gamma [181,182], PP2A [178,183], and the pol II CTD phosphatase FCP1 [184], also interact with splicing factors or are known to control splicing. Of these, PP2A binds CaMK IV in a signalling complex [185,186].…”
Section: Splicing Factors Regulated By Ca ++ Signalsmentioning
confidence: 99%
“…Using an RT-PCR-based assay (Fig. 1, A and B), it was found that overnight treatment of A549 lung adenocarcinoma cells with 20 M D-e-C 6 ceramide (sub-IC 50 dose for a 24-h period in A549 cells) (IC 50 ϭ 37 M) resulted in altering the ratio of the splice variants of Bcl-x and caspase 9 ( Fig. 2, A and B), but not Bax or caspase 2 (data not shown).…”
Section: Exogenous Ceramide Regulates the Alternative Splicing Ofmentioning
confidence: 99%
“…Endogenous ceramide has recently been found to modulate the phosphorylation status of SR proteins in a PP1-dependent manner (49). Several reports have also demonstrated a role for PP1 in regulating alternative splicing, and two spliceosomal targeting subunits for PP1 have been described (38,48,50,51). Therefore, PP1 may play a role in regulating RNA processing in response to stimuli, in particular, it may define a pathway linking ceramide to the regulation of the alternative splicing of apoptosis regulators.…”
mentioning
confidence: 99%
“…Furthermore, endogenous ceramide has been found recently to modulate the phosphorylation status of SR proteins in a PP1-dependent manner (26). PP1 also associates with the splice factor, PTB-associated splicing factor (PSF), and the PP1 regulatory subunit, nuclear inhibitor of PP1 (NIPP1), has been demonstrated to co-localize with splicing factors (15,25,27,28). Finally, dephosphorylation of SR proteins stimulated by PP1 induces alternative 5Ј splice site selection in adeno pre-mRNA in vitro, demonstrating that pre-mRNA splicing events are regulated in a phosphorylationdependent manner (29).…”
mentioning
confidence: 99%